2004
DOI: 10.1007/s00292-004-0687-4
|View full text |Cite
|
Sign up to set email alerts
|

Plazenta bei Schwangerschaftshochdruck

Abstract: At an incidence of 3.2-4% world-wide, pregnancy-induced hypertension (PIH) is the most common disease of pregnancy. Since this holds a risk, not only for the mother, but also for the child, the placenta should undergo pathological-anatomical examination in every case. Pathomorphological findings can be described in the feto-maternal border zone as well as in the fetal placenta. These are not, however, specific, nor do they offer diagnostic proof. Pathomorphological findings in the feto-maternal border zone: de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A plausible mechanism for the associations of pre‐eclampsia and gestational hypertension with MAFLD may be that they result in adverse vascular changes and placental hypoperfusion and thereby lead to fetal hypoxia and growth restriction. 30 , 31 , 32 , 33 Suboptimal oxygenation and growth of the fetus have been found to increase the offspring's risk of NAFLD in animal models 34 , 35 and in epidemiological studies. 11 , 12 Hence, albeit we found no difference in birth anthropometric measures between children with and without MAFLD, subclinical placental dysfunction may contribute to the observed associations of gestational hypertension and pre‐eclampsia with MAFLD, and is an important area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…A plausible mechanism for the associations of pre‐eclampsia and gestational hypertension with MAFLD may be that they result in adverse vascular changes and placental hypoperfusion and thereby lead to fetal hypoxia and growth restriction. 30 , 31 , 32 , 33 Suboptimal oxygenation and growth of the fetus have been found to increase the offspring's risk of NAFLD in animal models 34 , 35 and in epidemiological studies. 11 , 12 Hence, albeit we found no difference in birth anthropometric measures between children with and without MAFLD, subclinical placental dysfunction may contribute to the observed associations of gestational hypertension and pre‐eclampsia with MAFLD, and is an important area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that downregulation of amino acid transporters [35–40], lowered fetomaternal blood flow [35, 41], and structural abnormalities are present in IUGR placentas [4244]. Since the placenta is the medium through which the fetus receives all factors necessary for growth, disruptions in placental structure or function may alter the development of fetal vasculature, organs, or signaling pathways in ways that predispose the fetus to later development of hypertension.…”
Section: Uteroplacental Insufficiency and Hypertensionmentioning
confidence: 99%